Transações com partes relacionadas : determinantes e impactos no desempenho das empresas - Souza, João Antônio Salvador de (2014)
The international literature that examines the factors impacting related parties transactions focuses on the UK, US and Asia, and Brazil is an environment little investigated. This research aims to investigate both the impacting factors of contracts with related parties, and the impact of these transactions on the performance of Brazilian companies. Studies recent that investigated the determinants of related parties transactions (RPTs), as well as its impact on business performance, took into account the aspects presented by Gordon, Henry and Palia (2004): (a) conflict of interests, which support the view that the RPTs are harmful to minority shareholders, implying expropriation of their wealth by controlling (majority shareholders); and (b) efficient transactions that may be beneficial to companies, serving thus to economic objectives. This research draws on aspects of conflict of interest, based on agency theory and the fact that the Brazilian scenario is characterized by concentrated ownership and a legal environment characterized by poor protection of minority shareholders. To operationalize the research, we used an initial sample consisted of 70 companies listed on the BM&FBovespa observing the period from 2010 to 2012. The contracts listed were identified and quantified in two ways, according to the methodology applied by Kohlbeck and Mayhew (2004; 2010) and Silveira, Prado and Sasso (2009). As major determinants were investigated proxies to capture the effects of corporate governance mechanisms and legal environment of business performance, the control rights and cash flow rights mismatch and excessive executive compensation. Control variables to isolate the intrinsic characteristics of the firms were also added. In the econometric analysis Poisson models, clustered cross section (Pooled-OLS) and logit models were estimated. The estimation was done by the method of ordinary least squares (OLS), and to increase the robustness of the econometric estimates, instrumental variables with generalized method of moments (GMM) were used. Evidence indicates that investigated factors impact differently the various RPT measures of the companies analyzed. It was found that the contracts, in general, are damaging to companies, negatively impacting their performance, and this performance is increased by the presence of effective corporate governance. The results of the impact of corporate governance measures and the intrinsic characteristics of the firms in business performance are robust to the presence of endogeneity based on regressions with instrumental variables.